Introduction of Concept Mapping as an Innovative Tool to Enhance Learning Outcome in the Medical Students (International Journal of Physiology, 2019)
IntroductionIn today's multifaceted & challenging context of medical education, students are unable to organise, integrate information to the medical problems, so a need to fill this gap is strongly felt. The purpose of this study was to evaluate the effectiveness of Concept Mapping (CM) over the traditional method of teaching & learning.Aims & ObjectivesTo compare learning by traditional lecture with lecture using CM. To foster meaningful learning using CM & boosting the relevance of topic. To obtain feedback & reflection for CM based learning.Materials & MethodTotal 112 students were taken for the study. They were divided randomly in two groups. For group-A, lecture on Systemic lupus erythematous was taken by traditional method of teaching. For group-B lecture was taken by using concept mapping of same topic. Post-test (10 Marks MCQs) was taken from both groups & comparing was done. Cross over study was conducted for ethical purpose. Reflection & feedback was taken from students about CM.ResultThe result of post-test shows significant (P